Absence of association between serve and winning point in professional padel - Miguel, I. M.; Muñoz, D.; Lupo, C.; Alcaraz, B. J. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: The aim of this study was to analyze the efficiency of the serve in relation to different tactical parameters in men`s professional padel. METHODS: A total of 1089 points - from 217 games and 19 sets - from 8 World Padel Tour matches played in 2020 were analyzed by systematic observation. RESULTS: The results showed that the ordinary number of the set influences the efficiency of the serve (P=0.015) with more points won on serve during the second one, and more points lost during the third one. Differently, no difference emerged for the serve efficiency in terms of situation (P=0.233). Similarly, the serving situation does not affect the efficiency in key points (P=0.097) and in non-key points (P=0.706), producing more equality in Australian formation in key points. The direction of the serve in Australian formation (P=0.351) and conventional (P=0.32) does not affect its effectiveness, without effects for the second shot after the return in Australian formation (P=0.472) and conventional (P=0.458), being in both cases the backhand volley the most frequent stroke, for which the pair lose more points when serving. The number of strokes per point is associated to a higher probability of winning the point, being the number of strokes from 3 to 10 where the serving partner maintains the advantage, losing it from that stroke, in addition, there are no winning points neither with the serve nor with the serve-return. CONCLUSIONS: There are no significant differences (but only small divergences) in most of the tactical parameters considered in terms of serve efficiency.